Influence of COPD on the Diaphragm and Muscles of the Lower Limbs - A Meridj; R Belaala; Y Djeghri (Journal of Pulmonology and Respiratory Research, 2024)
Agusti A, Celli BR, Criner GJ, Halpin D, Anzueto A, Barnes P, et al. Global initiative for chronic obstructive lung disease 2023 report: GOLD executive summary. Am J Respir Crit Care Med. 2023;207(7):819-837. Available from: https://doi.org/10.1164/rccm.202301-0106ppMurray CJL, Aravkin AY, Zheng P, Abbafati C, Abbas KM, Abbasi-Kangevari M, et al. Global burden of 87 risk factors in 204 countries and territories, 1990–2019: a systematic analysis for the Global Burden of Disease Study 2019. Lancet. 2020;396(10258):1223-1249. Available from: https://pubmed.ncbi.nlm.nih.gov/33069327/Ho T, Cusack RP, Chaudhary N, Satia I, Kurmi OP. Under- and over-diagnosis of COPD: a global perspective. Breathe (Sheff). 2019;15(1):24-35. Available from: https://doi.org/10.1183/20734735.0346-2018Buist AS, Vollmer WM, McBurnie MA. Worldwide burden of COPD in high- and low-income countries. Part I. The Burden of Obstructive Lung Disease (BOLD) Initiative. Int J Tuberc Lung Dis. 2008;12(7):703-708. Available from: https://pubmed.ncbi.nlm.nih.gov/18544191/Halpin D, Celli B, Criner G, Frith P, Varela L, Salvi S, et al. The GOLD Summit on chronic obstructive pulmonary disease in low- and middle-income countries. Int J Tuberc Lung Dis. 2019;23(11):1131-1141. Available from: https://doi.org/10.5588/ijtld.19.0397Rehman AU, Hassali MAA, Muhammad SA, Harun SN, Shah S, Abbas S. The economic burden of chronic obstructive pulmonary disease (COPD) in Europe: results from a systematic review of the literature. Eur J Health Econ. 2020;21(2):181-194. Available from: https://doi.org/10.1007/s10198-019-01119-1Uzaslan E, Mahboub B, Beji M, Nejjari C, Tageldin MA, Khan JA, et al. The burden of chronic obstructive pulmonary disease in the Middle East and North Africa: results of the BREATHE study. Respir Med. 2012;106(Suppl). Available from: https://doi.org/10.1016/s0954-6111(12)70014-8Khelafi R, Aissanou A, Tarsift S, Skander F. Épidémiologie de la bronchopneumopathie chronique obstructive dans la wilaya d’Alger. Rev Mal Respir. 2011;28(1):32-40. Available from: http://dx.doi.org/10.1016/j.rmr.2010.06.026Decramer M, Janssens W. Chronic obstructive pulmonary disease and comorbidities. Lancet Respir Med. 2013;1(1):73-83. Available from: https://doi.org/10.1016/s2213-2600(12)70060-7Waschki B, Kirsten A, Holz O, Muller K-C, Meyer T, Watz H, et al. Physical activity is the strongest predictor of all-cause mortality in patients with COPD: a prospective cohort study. Chest. 2011;140(2):331-42. Available from: https://doi.org/10.1378/chest.10-2521Spruit MA, Gosselink R, Troosters T, Kasran A, Gayan-Ramirez G, Bogaerts P, et al. Muscle force during an acute exacerbation in hospitalized patients with COPD and its relationship with CXCL8 and IGF-I. Thorax. 2003;58(9):752-756. Available from: https://doi.org/10.1136/thorax.58.9.752Van Vliet M, Spruit MA, Verleden G, Kasran A, Van Herck E, Pitta F, et al. Hypogonadism, quadriceps weakness, and exercise intolerance in chronic obstructive pulmonary disease. Am J Respir Crit Care Med. 2005;172(9):1105-1111. Available from: https://doi.org/10.1164/rccm.200501-114ocCoronell C, Orozco‐Levi M, Mendez R, Ramirez‐Sarmiento A, Galdiz J, Gea J. Relevance of assessing quadriceps endurance in patients with COPD. Eur Respir J. 2004;24(1):129-136. Available from: https://doi.org/10.1183/09031936.04.00079603Vestbo J, Prescott E, Almdal T, Dahl M, Nordestgaard BG, Andersen T, et al. Body mass, fat-free body mass, and prognosis in patients with chronic obstructive pulmonary disease from a random population sample: findings from the Copenhagen City Heart Study. Am J Respir Crit Care Med. 2006;173(1):79-83. Available from: https://doi.org/10.1164/rccm.200506-969ocSeymour J, Spruit M, Hopkinson N, Natanek S, Man W-C, Jackson A, et al. The prevalence of quadriceps weakness in COPD and the relationship with disease severity. Eur Respir J. 2010;36(1):81-88. Available from: https://doi.org/10.1183/09031936.00104909Bernard S, LeBlanc P, Whittom F, Carrier G, Jobin J, Belleau R, et al. Peripheral muscle weakness in patients with chronic obstructive pulmonary disease. Am J Respir Crit Care Med. 1998;158(2):629-634. Available from: https://doi.org/10.1164/ajrccm.158.2.9711023Nici L, Donner C, Wouters E, Zuwallack R, Ambrosino N, Bourbeau J, et al. American Thoracic Society/European Respiratory Society statement on pulmonary rehabilitation. Am J Respir Crit Care Med. 2006;173(12):1390-1413. Available from: https://doi.org/10.1164/rccm.200508-1211stPitta F, Troosters T, Spruit MA, Probst VS, Decramer M, Gosselink R. Characteristics of physical activities in daily life in chronic obstructive pulmonary disease. Am J Respir Crit Care Med. 2005;171(9):972-977. Available from: https://doi.org/10.1164/rccm.200407-855ocMarquis K, Debigare R, Lacasse Y, LeBlanc P, Jobin J, Carrier G, et al. Midthigh muscle cross-sectional area is a better predictor of mortality than body mass index in patients with chronic obstructive pulmonary disease. Am J Respir Crit Care Med. 2002;166(6):809-813. Available from: https://doi.org/10.1164/rccm.2107031Maynard-Paquette A-C, Poirier C, Chartrand-Lefebvre C, Dube B-P. Ultrasound evaluation of the quadriceps muscle contractile index in patients with stable chronic obstructive pulmonary disease: relationships with clinical symptoms, disease severity and diaphragm contractility. Int J Chron Obstruct Pulmon Dis. 2020;15:79-88. Available from: https://doi.org/10.2147/copd.s222945McCool FD, Tzelepis GE. Dysfunction of the diaphragm. N Engl J Med. 2012;366(10):932-42. Available from: https://doi.org/10.1056/nejmra1007236Charloux A, Enache I. Exploration fonctionnelle des muscles respiratoires. EMC-Pneumologie. 2015;12(3):1-11. Available from: https://www.em-consulte.com/article/983785/exploration-fonctionnelle-des-muscles-respiratoireDe Blasio F, Comune M, Oliva A, Garello L, Bucca C, Prota R. Influence of diaphragm dysfunction, exercise capacity, and nutrition on dyspnea severity of COPD patients. Chest. 2020;157(6). Available from: http://dx.doi.org/10.1183/13993003.congress-2020.1025Similowski T, Yan S, Gauthier AP, Macklem PT, Bellemare F. Contractile properties of the human diaphragm during chronic hyperinflation. N Engl J Med. 1991;325(13):917-923. Available from: https://doi.org/10.1056/nejm199109263251304Levine S, Nguyen T, Kaiser LR, Rubinstein NA, Maislin G, Gregory C, et al. Human diaphragm remodeling associated with chronic obstructive pulmonary disease: clinical implications. Am J Respir Crit Care Med. 2003;168(6):706-713. Available from: https://doi.org/10.1164/rccm.200209-1070ocBarreiro E, De La Puente B, Minguella J, Corominas JM, Serrano S, Hussain SN, et al. Oxidative stress and respiratory muscle dysfunction in severe chronic obstructive pulmonary disease. Am J Respir Crit Care Med. 2005;171(10):1116-1124. Available from: https://doi.org/10.1164/rccm.200407-887ocLevine S, Gregory C, Nguyen T, Shrager J, Kaiser L, Rubinstein N, et al. Bioenergetic adaptation of individual human diaphragmatic myofibers to severe COPD. J Appl Physiol. 2002;92(3):1205-1213. Available from: https://doi.org/10.1152/japplphysiol.00116.2001Barnes PJ. Oxidative stress in chronic obstructive pulmonary disease. Antioxidants. 2022;11(5):965. Available from: https://doi.org/10.3390%2Fantiox11050965Scicchitano BM, Pelosi L, Sica G, Musaro A. The physiopathologic role of oxidative stress in skeletal muscle. Mech Ageing Dev. 2018;170:37-44. Available from: https://doi.org/10.1016/j.mad.2017.08.009Lage VKdS, de Paula FA, dos Santos JM, Costa HS, da Silva GP, Lima LP, et al. Are oxidative stress biomarkers and respiratory muscle strength associated with COPD-related sarcopenia in older adults? Exp Gerontol. 2022;157:111630. Available from: https://doi.org/10.1016/j.exger.2021.111630Sepulveda‐Loyola W, Osadnik C, Phu S, Morita AA, Duque G, Probst VS. Diagnosis, prevalence, and clinical impact of sarcopenia in COPD: a systematic review and meta‐analysis. J Cachexia Sarcopenia Muscle. 2020;11(5):1164-1176. Available from: https://doi.org/10.1002/jcsm.12600Wormser J, Lebret M, Le Neindre A. L’échographie du diaphragme: principes et intérêts pour le kinésithérapeute. Kinésithérapie, la Revue. 2017;17(182):62-70. Available from: https://doi.org/10.1016/j.kine.2016.11.009Gethin-Jones TL, Noble VE, Morse CR. Quantification of diaphragm function using ultrasound: evaluation of a novel technique. Ultrasound Med Biol. 2010;36(11):1965-1969. Available from: https://doi.org/10.1016/j.ultrasmedbio.2010.08.003Matamis D, Soilemezi E, Tsagourias M, Akoumianaki E, Dimassi S, Boroli F, et al. Sonographic evaluation of the diaphragm in critically ill patients: technique and clinical applications. Intensive Care Med. 2013;39(5):801-810. Available from: https://doi.org/10.1007/s00134-013-2823-1Kim WY, Suh HJ, Hong S-B, Koh Y, Lim C-M. Diaphragm dysfunction assessed by ultrasonography: influence on weaning from mechanical ventilation. Crit Care Med. 2011;39(12):2627-2630. Available from: https://doi.org/10.1097/ccm.0b013e3182266408Epelman M, Navarro OM, Daneman A, Miller SF. M-mode sonography of diaphragmatic motion: description of technique and experience in 278 pediatric patients. Pediatr Radiol. 2005;35(7):661-667. Available from: https://doi.org/10.1007/s00247-005-1433-7Richard P. Exploration du diaphragme: l’échographie est incontournable. Rev Mal Respir. 2017;34(6):645-660. Available from: http://dx.doi.org/10.1016/j.rmr.2017.02.005